E-Module Social Studies Containing Balinese Folk Tales Based on Pancasila Student Profiles for Grade V Students in Elementary Schools - Sinta Dewi, Ida Ayu Agung Paramita; I Gusti Agung Ayu Wulandari; Didith Pramunditya Ambara (Jurnal Pendidikan Multikultural Indonesia, 2024)
This  study  was  motivated  by  the  low  interest  and  motivation  of  elementary  school  students  in  learning  Social  Studies  (IPS),  which  is  largely  due  to  the  limited  variety  of  instructional  media  and  reliance  on  textbooks.  The  main  objective  of  this  research  is  to  develop  and  examine  the  feasibility  and  effectiveness  of  a  Social  Studies  e-module  incorporating  Balinese  folktales  based  on  the  Pancasila  Student  Profile  to  enhance  the  competence  and  learning  interest  of  fifth-grade  students.  This  research  employed  a  Research  and  Development  (R&D)  design  using  the  Dick  and  Carey  model.  The  study  involved  58  fifth-grade  students,  divided  into  a  control  group  (VA)  and  an  experimental  group  (VB).  Data  were  collected  through  tests,  questionnaires,  and  expert  validations  using  instruments  such  as  validation  sheets,  learning  outcome  tests,  and  student  response  questionnaires.  Data  analysis  was  conducted  using  both  descriptive  (qualitative  and  quantitative)  and  inferential  statistical  methods.  The  results  showed  that  the  developed  e-module  was  highly  feasible,  with  validation  scores  of  92%  (content  expert),  95%  (media  expert),  95%  (language  expert),  94.16%  (individual  trials),  and  90%  (small  group  trials).  The  effectiveness  test  indicated  a  significant  difference  between  the  experimental  and  control  groups  (significance  value  <  0.05).  The  findings  conclude  that  the  e-module  integrating  Balinese  folktales  and  the  Pancasila  Student  Profile  is  effective  in  improving  students’  competence  and  interest  in  Social  Studies  learning.  The  implication  of  this  study  underscores  the  importance  of  incorporating  contextual,  character-based  local